PEMANFAATAN BIJI KELOR SEBAGAI KOAGULAN PADA PROSES KOAGULASI LIMBAH CAIR INDUSTRI TAHU DENGAN MENGGUNAKAN JAR TEST - Riko Putra; Buyung Lebu; MHD Darwis Munthe; Ahmad Mulia Rambe (Talenta Publisher (Universitas Sumatera Utara), 2013)
For a long time the use of moringa seed as waste rarely used, needs developing further to process liquid waste more economically and environmentally friendly. The research was done to find the effect of moringa seed as coagulant and the precipitation time to the turbidity decrease percentage, TSS and COD of liquid waste of whey industry by using the coagulation-flocculation method. The research variables are moringga seed dose (2000, 3000, 4000, 5000 and 6000 mg/liter of liquid waste of whey industry), the precipitation time (50, 60 and 70 minutes) with the particle size of 50 mesh and pH used is pH of liquid waste of whey industry. The research used the jar test tool. The data analysis was done graphically. The result of the research showed that in the range of time the observation was done, the moringa seed dose as an optimal coagulant being 3000 mg/liter of the liquid waste of whey industry in the precipitation time of 50 minutes could set aside the turbidity over 89,42%, TTS over 98,73% and COD over 69,58%.